Assessing the macroeconomic impact of weather shocks in Colombia - José Vicente Romero; Sara Naranjo-Saldarriaga; Jonathan Alexander Mu\~noz (Graduate Institute of International and Development Studies, 2023)
In this paper, we investigate the impact of adverse weather shocks on Colombian economic activity, with a particular emphasis on the effects on agricultural output, food and headline inflation. Existing literature and empirical evidence suggest that adverse weather shocks, such as those related to the El Ni\~no event in 2015-2016, lead to decreases in agricultural output and increases in inflation without significantly affecting total GDP growth. To further assess this result, we evaluate the impact of ENSO fluctuations using a BVAR-X model. Based on these findings, we propose a small open economy New Keynesian model that introduces a novel channel through which relative prices (agricultural vs. non-agricultural) are affected by weather shocks, allowing us to incorporate this empirical evidence into a structural model for Colombia.
Keywords: Q54; E52; E31; 330; Weather shocks; El Ni\~no Southern Oscillation (ENSO); Small Open Economy New Keynesian Models